Distribusi dan Prevalensi Infeksi Oportunistik pada Orang dengan HIV/AIDS di RSUD Gambiran, Kediri, Jawa Timur - Novrindo Sidjabat, Forman; Lestari Nur Jannah, Fitria Pratama (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2025)
Introduction: HIV/AIDS remains a global health problem with opportunistic infections (OIs) contributing to increased mortality. As a referral center for HIV/ AIDS services in Kediri City, Gambiran Hospital has reported a rising prevalence of HIV/AIDS and associated OIs. This study aimed to determine the prevalence and distribution of OIs among HIV/AIDS patients at Gambiran Hospital, Kediri, East Java.Method: This study involved adult patients diagnosed with HIV/AIDS and OIs during the period 2019–2021. Sampling from medical records was performed using a proportional random sampling method. Data were analyzed descriptively.Results: Of the total subjects (n = 59), the highest proportion of HIV/AIDS patients with OIs was found in group age of 26–45 years (62.7%). Most were male (66.1%), married (71.2%), actively employed (66.1%), and had completed high school (45.8%). The majority of subjects had a single OI (61%), with tuberculosis being the most common (34.9%).Conclusion: HIV/AIDS patients with OIs at Gambiran Hospital were predominantly aged 26–45 years, male, married, actively employed, and had completed high school, with tuberculosis being the most common OI.